Global value chains participation and structural transformation in Africa: Are we advocating environmental protection? - Ali, Essossinam; Gniniguè, Moukpè (Journal of cleaner production, 2022)
The environmental policy in Global Value Chains (GVCs) participation and structural transformation of African countries has been hardly investigated. The study analyzes the effect of GVCs participation on the structural transformation of African economies. It also examines the effect of structural transformation on environmental pollution and assesses whether African countries are advocating the environmental issues while seeking structural transformation through GVCs participation. We used second-generation panel data for 41 African countries from 1990 to 2018 and found that GVCs participation, digitalization, and renewable energy are key determinants of structural transformation in Africa. The results revealed that GVCs participation is subject to environmental pollution and the U-inverted hypothesis between GDP and CO2 emissions is verified. Moreover, we find that the moderating effect of the structural transformation on the effect of GVCs participation on environmental pollution in Africa is negative. This result suggests that pursuing the structural transformation in African economies can play a key role in reducing environmental pollution which is highly correlated with GVCs participation. Findings show that the use of renewable energy can significantly reduce CO2 emissions. The results are robust whether we consider the backward or forward linkages. These results have important policy implications in terms of upgrading opportunities to reduce emissions and promote green development for the structural transformation of African countries throughout GVCs participation.